1997
DOI: 10.1159/000044874
|View full text |Cite
|
Sign up to set email alerts
|

Renal Trauma and the Risk of Long-Term Complications in Shock Wave Lithotripsy

Abstract: Open surgery for removal of upper urinary tract stones has long been associated with a high morbidity and mortality. So when shock wave (SW) lithotripsy (SWL) was introduced in the early 1980s, the climate was right for acceptance of a noninvasive method for stone comminution. The growth in popularity of SWL was extremely rapid, based in part on the perception that it was entirely safe [1]. Now, after a decade of clinical SWL, experience tells us differently. SWL may be very effective at breaking kidney stones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
124
0
5

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 184 publications
(132 citation statements)
references
References 25 publications
3
124
0
5
Order By: Relevance
“…This image is also representative of another important observation: Large blood vessels, bile ducts, or other soft tissue inhomogeneities located prefocally in the acoustic path did not interfere with the lesion formation. Similar effects of selective tissue damage caused by ultrasound-mediated therapies have been observed in extracorporeal shock wave lithotripsy (22) and, recently, in cavitation cloud histotripsy as well (23).…”
Section: Large Vessels and Biliary Structures Adjacent To The Lesion supporting
confidence: 62%
“…This image is also representative of another important observation: Large blood vessels, bile ducts, or other soft tissue inhomogeneities located prefocally in the acoustic path did not interfere with the lesion formation. Similar effects of selective tissue damage caused by ultrasound-mediated therapies have been observed in extracorporeal shock wave lithotripsy (22) and, recently, in cavitation cloud histotripsy as well (23).…”
Section: Large Vessels and Biliary Structures Adjacent To The Lesion supporting
confidence: 62%
“…However, study of stone breakage in vitro has shown that COM stones vary dramatically in their fragility to SW's, with some stones being very resistant, and others quite fragile [5,6], and this variability is consistent with clinical experience [4]. Lithotripter SW's can produce adverse effects [7], so it is important to consider ways to reduce dosage of SW's when possible. If the level of susceptibility of a given COM stone to SW lithotripsy could be established at diagnosis, SW dosage could be tailored to that case.…”
Section: Introductionmentioning
confidence: 78%
“…At that time it was already known that some stones could be SW-resistant, and it was thought that x-ray at diagnosis could be used to avoid subjecting the patient to an ineffective procedure. It is now known that lithotripter SW's can cause significant renal injury [7], and that SW trauma may be contributory to subsequent development of other disorders [24,25]. Thus, the application of unnecessary SW's should be considered a risk to the patient, and it would be of value to determine in advance the dose of SW's required for a given stone.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 The significance of the tissue damage is still under debate, as are the mechanisms which produce it. 5,6 In addition there is no agreement as to the mechanism by which the shock waves comminute calculi. 7 The groups involved in this manuscript are part of a multi-institutional research program to address issues in SWL.…”
Section: Introductionmentioning
confidence: 99%